Temperamental correlates and predictors of toddler adaptation to nursery - Świdrak, Ewelina (Revija za elementarno izobraževanje, 2026)
This study aimed to analyse the relationship between children’s adaptation to nursery and children’s temperament. The results show a statistically significant relationship between children’s shyness and emotionality and the time of adaptation to nursery. Shy children displayed more negative and less positive behaviours during adaptation. Children with less control over their emotional reactions showed more negative emotions and behaviours during separation from their parents. Moreover, further statistical analysis divided by sex showed that the older and shier the boys were, the more negative behaviours they displayed - as perceived by the nursery staff - during nursery adaptation.
Keywords: early childhood; Otroške jasli; Predšolski otroci; Prilagajanje (psihologija); temperament; zgodnje otroštvo